Unveiling microscale aerosol formation pathways in combustion systems: in situ evidence from cigarette burning cones - Jiaying Li; Huapeng Cui; Meijuan Fan; Li Chen; Yaqiong Qin; Ruihong Liu; Mantang Chen; Yu Liu; Jizhao Guo; Shaofeng Liu; Xiaobing Zhang; Fuwei Xie; et al. (Biomass and Bioenergy, 2026)

Noncovalent interaction between β-conglycinin and rutin: Structural characterization, binding mechanism and emulsifying stability - Fuwei Sun; Haotian Liu; Chaojiang Dong; Yang Li; Zengwang Guo; Lianzhou Jiang; Zhongjiang Wang; Fang Kou (Food Hydrocolloids, 2026)

Leonurine-ligated nanozymes: A feasible therapeutic avenue for anti-inflammatory intervention in Parkinson's disease - Yingying Wang; Qing Liu; Chang Liu; Xiaoxi Chen; Ruijun Li; Wanying Chen; Fuwei Yang (Chemical Engineering Journal, 2026)

Cavitation jet-assisted construction of the soybean protein-based high internal phase emulsions: interfacial behaviors, formation mechanisms in 3D printing and improved bioaccessibility of γ-oryzanol - Fuwei Sun; Fang Kou; Yiying Jin; Meiyun Li; Caihua Liu; Meng Yuan; Lianzhou Jiang; Zengwang Guo; Zhongjiang Wang; Haotian Liu (Food Hydrocolloids, 2026)

Analysis and identification of geographical indication protected Huangjiu based on multimodal data combined with chemometric methods - Xiaodan Liu; Qiuwen Shan; Xianhao Ding; Chao Ji; Yonghui Yu; Huang Dai; Fuwei Pi; Jiahua Wang; Ming Zhang (Food Control, 2026)

Spatiotemporal heterogeneity of synergetic enhancement in pollution and carbon reduction driven by environmental regulation: a marginal abatement cost perspective - Wei Shi; Jinling Yang; Fuwei Qiao; Zixia Yuan; Cuihua Jia; Chengcheng Liu (Clean Technologies and Environmental Policy, 2026)

Development of a mechanistic framework for occupational safety and health risk management in lithium-ion battery manufacturing facilities based on inherent safety concepts - Wei Pu; Huhua Liu; Peng Wang; Houjiang Fan; Xiaoming Gao; Fuwei He; Yukun Sun; Zongyou Zhang; Mengting Huang (Process Safety and Environmental Protection, 2026)

A novel 3D-printed flexible electrode with rGO/MWCNTs ink for capsaicin detection in chilli peppers - Jiachen Zhao; Huilin Hu; Chao Wang; Yingting Li; Xueyu Jiang; Ming Zhang; Fangkai Han; Ning Yang; Xiaodan Liu; Jiahua Wang; Yingli Wang; Shuo Duan; et al. (Food Chemistry, 2026)

The critical role of alkaline microenvironment in advanced oxidation processes: A case study of calcium carbonate polymorphs - Ziyang Chu; Haibo Liu; Tianhu Chen; Xuehua Zou; Fuwei Sun; Dong Chen (Journal of Environmental Chemical Engineering, 2026)

High internal phase Pickering emulsions for 3D printing constructed from enzyme deamidated peanut protein microgel particles - Jinrui Hu; Yapeng Liu; Yanan Guo; Lulu Shen; Fuwei Sun; Lianzhou Jiang; Zhongjiang Wang; Zengwang Guo (Food Hydrocolloids, 2026)

A non-destructive workflow integrating X-ray computed tomography and machine learning for multi-defect identification and kernel plumpness assessment of in-shell walnuts - Menglong Ma; Ming Zhang; Haitao Fu; Yixiao Wang; Ning Yang; Huang Dai; Fuwei Pi; Xiaodan Liu; Jiahua Wang (Food Control, 2026)

Effect of dextran molecular weight on Maillard glycation of soy protein isolate: Structural modifications and flavor-binding behavior - Xuejie Li; Yaqiong Qin; Bing Wang; Cong Wang; Mantang Chen; Ruihong Liu; Kejian Liu; Cong Nie; Fuwei Xie; Xiaoyu Wang; Wentao Zhang; Jian Li (Food Hydrocolloids, 2026)

Simultaneous non-destructive detection of watercore and bruising in ‘Fuji’ apples via X-Ray computed tomography: Dual-threshold segmentation and machine learning classification - Haitao Fu; Menglong Ma; Yixiao Wang; Ziwei Wang; Jun Wang; Xiaodan Liu; Huang Dai; Fuwei Pi; Jiahua Wang; Ming Zhang (Postharvest Biology and Technology, 2026)

Strategy comparison for purifying phycocyanin from microplastic-contaminated Spirulina platensis: A dual evaluation of product quality and microplastic removal - Zhiheng Yue; Yixiao Wang; Yuhang Zhao; Huang Dai; Xiaodan Liu; Fuwei Pi; Xin Liu; Jiahua Wang (Food Chemistry, 2025)

A β-cyclodextrin/fluorinated covalent triazine framework hybrid fiber for synergistic solidphase microextraction of aflatoxins in cereals - Lining Pan; Kunling Liu; Bing Wang; Nan Wang; Fuwei Xie; Cong Nie; Yaqiong Qin; Xiaoyu Wang; Wenjie Zhao (Food Chemistry, 2025)

Sensitive dual detection of N-nitrosodiphenylamine and N-nitrosodiethylamine using a PtNPs-enhanced MWCNTs/Fe-porphyrinic MOF nanocomposite-based electrochemical sensor - Jiachen Zhao; Yue Zou; Junlan Yu; Chao Wang; Yili Hu; Fangkai Han; Ning Yang; Fuwei Pi; Ming Zhang; Xiaodan Liu; Jiahua Wang; Huang Dai; et al. (Food Chemistry, 2025)

Synergistic enhancement of 3D printing performance in soybean protein isolate gel inks by lonic/nonionic polysaccharides: A network rearrangement mechanism revealed by rheology and the sequence of physical processes analysis - Fangxiao Lou; Yanan Guo; Shuo Zhang; Fuwei Sun; Jun Liu; Lianzhou Jiang; Zengwang Guo; Zhongjiang Wang (Food Hydrocolloids, 2025)

Soy protein isolate gel improved with carrageenan-assisted limited enzymatic hydrolysis: Gelation properties and binding abilities with selected flavour compounds - Shuo Zhang; Sibo Liu; Fangxiao Lou; Fuwei Sun; Qi Gong; Daoying Wang; Zhongjiang Wang; Zengwang Guo (Food Hydrocolloids, 2025)

Nondestructive classification of internal defects in camellia seeds and chestnuts using X-ray imaging: optimization and comparison of deep learning classifiers - Menglong Ma; Haitao Fu; Yixiao Wang; Zelin Lu; Ziwei Wang; Jingjing Cheng; Xiaodan Liu; Huang Dai; Fuwei Pi; Jiahua Wang (Food Control, 2025)

Efficient degradation of sulfamethazine sodium via hydrogen peroxide activation in the presence of calcite: Synergistic effect of Co(II) and Cu(II) - Ping Zhang; Xinru Yang; Can Wang; Fuwei Sun; Haibo Liu; Tianhu Chen; Dong Chen; Ziyang Chu; Jin Zhang; Jian Huang; Fazhi Xie (Journal of Water Process Engineering, 2025)

Integrating random forest and network stability analysis: Microbial mechanisms of petroleum hydrocarbon-benzene degradation in Yellow River Delta soils - Huanxin Zhang; Youru Zhang; Fuwei Gao; Shudi Yao; Yumiao Zhou; Jizhuang Chu; Qing Liu; Qiang Kong (Process Safety and Environmental Protection, 2025)

Canopy nitrogen and water addition affect fine-root survival strategies and carbon allocation in a warm-temperate forest in China - Wen Li; Yanzhu Su; Yiwen Qin; Fuwei Li; Tenglong Zhou; Yaqi He; Jianing Mao; Mengke Li; Chang Liu; Yifei Shi; Dandan Zhu; Chunyu Shen; et al. (Forest Ecology and Management, 2025)

Aptamer-modulated Pt/Au/MIL-100(Fe) nanozymatic activity for the colorimetric detection of deoxynivalenol in grains - Huang Dai; Junlan Yu; Run Zhou; Guijie Hao; Zhaohui Qiao; Zhe Feng; Xin Liu; Jie Bi; Jiahua Wang; Xiaodan Liu; Fuwei Pi; Yafang Shen (Food Chemistry, 2025)

The pH-sensitive polymerization process of phenol on hexagonal birnessite - Haibo Liu; Bo Chen; Ziyang Chu; Zhengyan Han; Fuwei Sun; Hao Wang; Xuehua Zou; Tianhu Chen (Journal of Environmental Management, 2025)

One pot preparation of magnetic benzylated cyclodextrin-based hyper-cross-linked polymer for phthalate esters extraction from tea beverages - Yaqiong Qin; Kunling Liu; Cong Nie; Fuwei Xie; Xiaoyu Wang; Ashraf Ali; Bing Wang; Qunye Hong; Wenjie Zhao (Food Chemistry, 2025)

High-throughput screening of acetals/ketals in edible essences via GC-Orbitrap-MS and their formation rates at room temperature - Xiaoyu Wang; Qiong Guo; Lining Pan; Cong Nie; Yiming Bi; Yaqiong Qin; Fuwei Xie; Fangqi Du; Yuhan Peng; Bing Wang; Ruihong Liu; Hui Wang; et al. (Food Chemistry, 2025)

Spotlight on the long-term effects of micro/nanoplastics exposure on Spirulina platensis: Algal cells, extracellular polymeric substances, and phycocyanin - Zhiheng Yue; Jiangjin Qian; Wenjing Li; Xiaodan Liu; Huang Dai; Xin Liu; Fuwei Pi; Jiahua Wang (Food Chemistry, 2025)

Fe1-xS@BC prepared from natural pyrite and biomass as peroxydisulfate activator for sulfadiazine degradation - Jintian Hao; Zhengyan Han; Hanlin Wang; Ziyang Chu; Tianhu Chen; Haibo Liu; Xuehua Zou; Dong Chen; Hao Wang; Fuwei Sun (Environmental Research, 2025)

Surface whitening prevention strategy of the mural relics from consolidation treatment: An innovative calcium protectant - Lu Wang; Zixuan Wang; Yating Wang; Guang Huang; Yalong Xing; Fuwei Yang; Zhang He; Yan Liu; Yifei Miao; Shaoxuan Niu (Chemical Engineering Journal, 2025)

Adulteration detection of multi-species vegetable oils in camellia oil using Raman spectroscopy: Comparison of chemometrics and deep learning methods - Jiahua Wang; Jiangjin Qian; Mengting Xu; Jianyu Ding; Zhiheng Yue; Yanpeng Zhang; Huang Dai; Xiaodan Liu; Fuwei Pi (Food Chemistry, 2025)

Upcycling CO2 and bio-derived furan into degradable plastic monomer via coupling of photocatalysis and thermocatalysis - Qi Liu; Chengyang Li; Tingting Wang; Peng Sun; Jia Wang; Yongjie Xi; Guang Gao; Mengnan Nie; Li Huang; Guofeng Wang; Zelun Zhao; Zhiwei Huang; et al. (Chemical Engineering Journal, 2024)

Additive patterns in near-infrared diffuse reflectance spectra: Implications for product formulation and analysis - Le Zhao; Youyan Liang; Nuohan Zhang; Yanbin Chang; Meijuan Fan; Cong Wang; Beibei Li; Hongbo Wang; Yu Liu; Hongxiao Yu; Song Yang; Fuwei Xie; et al. (Food Control, 2024)

Tunable magnetism and band structure in kagome materials RETi3Bi4 family with weak interlayer interactions - Jingwen Guo; Liqin Zhou; Jianyang Ding; Gexing Qu; Zhengtai Liu; Yu Du; Heng Zhang; Jiajun Li; Yiying Zhang; Fuwei Zhou; Wuyi Qi; Minghui Cui; et al. (Science Bulletin, 2024)

Autocatalytic degradation of Cu-EDTA in the Calcite/PMS system: Singlet oxygen and Cu(III) - Ziyang Chu; Zhengyan Han; Haibo Liu; Tianhu Chen; Xuehua Zou; Hanlin Wang; Fuwei Sun; Hao Wang; Dong Chen (Journal of Hazardous Materials, 2024)

Simultaneously enhancing the mechanical and thermoelectric properties of diketopyrrolopyrrole-thiophene based conjugated polymers through dynamic hydrogen-bonding - Xuyan Tang; Yufeng Wu; Guoliang He; Jiatao Wu; Fei Zhong; Zhibo Ren; Guibin Cao; Fuwei Liu; Chunmei Gao; Lei Wang (Chemical Engineering Journal, 2024)

A New Prediction Model for Cutting Depth of Hard Rock Using High-Pressure Water Jets - Fuwei Liu; Yansen Wang; Xin Huang; Guoxuan Song; Yuning Wang (Rock Mechanics and Rock Engineering, 2024)

Effect of glycosylation on soy protein isolate–sodium carboxymethyl cellulose conjugates heat-induced gels and their applications as carriers of riboflavin - Fuwei Sun; Jing Xu; Zhuying Wang; Tianfu Cheng; Daoying Wang; Jun Liu; Zengwang Guo; Zhongjiang Wang (Food Hydrocolloids, 2024)

Characterization of HIPEs stabilized by soy protein isolate with excellent rheological properties for 3D printing: Bridging the correlation among structure, function and application - Meng Yuan; Bailiang Li; Fuwei Sun; Tianfu Cheng; Jun Liu; Daoying Wang; Zengwang Guo; Zhongjiang Wang (Food Hydrocolloids, 2024)

Reducing microplastics in tea infusions released from filter bags by pre-washing method: Quantitative evidences based on Raman imaging and Py-GC/MS - Zhiheng Yue; Xiaodan Liu; Tingna Mei; Yanpeng Zhang; Fuwei Pi; Huang Dai; Yi Zhou; Jiahua Wang (Food Chemistry, 2024)

Investigation of the in vitro toxic effects induced by real-time aerosol of electronic cigarette solvents using microfluidic chips - Zezhi Li; Xiang Li; Boyang Feng; Junwei Zhao; Kejian Liu; Fuwei Xie; Jianping Xie (Food and Chemical Toxicology, 2024)

USP18 Curbs the Progression of Metabolic Hypertension by Suppressing JAK/STAT Pathway - Zhihong Xie; Mingshan Huang; Wang Xu; Fuwei Liu; Donghua Huang (Cardiovascular Toxicology, 2024)

Different responses of marine microalgae Phaeodactylum tricornutum upon exposures to WAF and CEWAF of crude oil: A case study coupled with stable isotopic signatures - Yadi Lou; Ying Wang; Shiyue Li; Fuwei Yu; Xing Liu; Yi Cong; Zhaochuan Li; Fei Jin; Mingxing Zhang; Ziwei Yao; Juying Wang (Journal of Hazardous Materials, 2024)

Simultaneous removal of lead, cadmium, and norfloxacin by Calcite/PMS system: Performance and mechanisms - Ziyang Chu; Haibo Liu; Tianhu Chen; Hanlin Wang; Fuwei Sun; Xuehua Zou; Dong Chen; Dionysios D. Dionysiou (Journal of Environmental Chemical Engineering, 2024)

Oral delivery of berberine by liver-targeted zwitterionic nanoparticles to overcome multi-intestinal barriers and extend insulin treatment duration - Yuhong Ma; Caihua Li; Fuwei Han; Yunzhu Liu; Umm E Hani; Yinan Zhong; Dechun Huang; Wei Chen; Hongliang Qian (Chemical Engineering Journal, 2024)

Cutting efficiency of extremely hard granite by high-pressure water jet and prediction model of cutting depth based on energy method - Fuwei Liu; Yansen Wang; Xin Huang (Bulletin of Engineering Geology and the Environment, 2024)

Analysis of the response to cigarette smoke exposure in cell coculture and monoculture based on bionic-lung microfluidic chips - Zezhi Li; Boyang Feng; Xiang Li; Junwei Zhao; Kejian Liu; Fuwei Xie; Jianping Xie (Analytica Chimica Acta, 2024)

Non-destructive detection and grading of chilling injury-induced lignification of kiwifruit using X-ray computer tomography and machine learning - Jiahua Wang; Yuqing Lin; Qiaocong Li; Zelin Lu; Jiangjin Qian; Huang Dai; Fuwei Pi; Xiaodan Liu; Yong He (Computers and Electronics in Agriculture, 2024)

Self-assembly kieselguhr-based ZSM-5 for catalytic pyrolysis of mask waste to produce high value-added aromatics - Yufei Gu; Hucheng Ge; Yuke Liu; Qi Wei; Tianhua Gao; Hengshuo Gu; Hongbing Fu; Fuwei Li; Hongfei Lin; Lei Miao; Zhixia Li (Fuel, 2024)

Interaction mechanism of pea proteins with selected pyrazine flavors: Differences in alkyl numbers and flavor concentration - Yanan Guo; Qi Gong; Fuwei Sun; Tianfu Cheng; Zhijun Fan; Zhaoxian Huang; Jun Liu; Zengwang Guo; Zhongjiang Wang (Food Hydrocolloids, 2024)

Progress on aptamer-based SERS sensors for food safety and quality assessment: methodology, current applications and future trends - Guoyong Jiang; Yu Li; Jinghan Liu; Ling Liu; Fuwei Pi (Critical Reviews in Food Science and Nutrition, 2024)

Fe3O4 derived from the decomposition of siderite as a heterogeneous photocatalyst to degrade 2,4-dichlorophenol via activating PMS - Hao Wang; Haibo Liu; Ziyang Chu; Fuwei Sun; Xuehua Zou; Qiang Wang; Tianhu Chen; Dong Chen; Hanlin Wang (Journal of Water Process Engineering, 2024)

Floating plants reduced methane fluxes from wetlands by creating a habitat conducive to methane oxidation - Fuwei Wang; Songhe Zhang; Xiuren Hu; Xin Lv; Min Liu; Yu Ma; Benjamin Manirakiza (Journal of Environmental Sciences, 2024)

In situ Raman characterization of the stability of blueberry anthocyanins in aqueous solutions under perturbations in temperature, UV, pH - Chuchu Duan; Xiaofeng Xiao; Yonghui Yu; Mengting Xu; Yanpeng Zhang; Xiaodan Liu; Huang Dai; Fuwei Pi; Jiahua Wang (Food Chemistry, 2024)

Gel properties of rice proteins-pectin composite and the delivery potential for curcumin: Based on different concentrations and the degree of esterification of pectin - Tianfu Cheng; Zhongjiang Wang; Fuwei Sun; Haotian Liu; Jun Liu; Zengwang Guo; Linyi Zhou (Food Hydrocolloids, 2024)

Combining a lung microfluidic chip exposure model with transcriptomic analysis to evaluate the inflammation in BEAS-2B cells exposed to cigarette smoke - Zezhi Li; Xiang Li; Boyang Feng; Jingxian Xue; Junwei Zhao; Qingqing Zhu; Kejian Liu; Fuwei Xie; Jianping Xie (Analytica Chimica Acta, 2024)

The pH-sensitive transformation of birnessite and its effect on the fate of norfloxacin - Qimengzi Wang; Zhengyan Han; Haibo Liu; Tianhu Chen; Xuehua Zou; Ziyang Chu; Jinchao Hu; Fuwei Sun; Hanlin Wang (Chemosphere, 2023)

Advances on removal of organophosphorus pesticides with electrochemical technology - Yuqi Wan; Jinghan Liu; Fuwei Pi; Jiahua Wang (Critical Reviews in Food Science and Nutrition, 2023)

Routine analysis of pesticides in foodstuffs: Emerging ambient ionization mass spectrometry as an alternative strategy to be on your radar - Jingkun Li; Jinghan Liu; Yuqi Wan; Jiahua Wang; Fuwei Pi (Critical Reviews in Food Science and Nutrition, 2023)

A Machine-Learning Approach Based on Attention Mechanism for Significant Wave Height Forecasting - Jiao Shi; Tianyun Su; Xinfang Li; Fuwei Wang; Jingjing Cui; Zhendong Liu; Jie Wang (Journal of Marine Science and Engineering, 2023)
Significant wave height (SWH) is a key parameter for monitoring the state of waves. Accurate and long-term SWH forecasting is significant to maritime shipping and coastal engineering. This study proposes a transformer model based on an attention mechanism to achieve the forecasting of SWHs. The transformer model can capture the contextual information and dependencies between sequences and achieves continuous time series forecasting. Wave scale classification is carried out according to the forecasting results, and the results are compared with gated recurrent unit (GRU) and long short-term memory (LSTM) machine-learning models and the key laboratory of MArine Science and NUmerical Modeling (MASNUM) numerical wave model. The results show that the machine-learning models outperform the MASNUM within 72 h, with the transformer being the best model. For continuous 12 h, 24 h, 36 h, 48 h, 72 h, and 96 h forecasting, the average mean absolute errors (MAEs) of the test sets were, respectively, 0.139 m, 0.186 m, 0.223 m, 0.254 m, 0.302 m, and 0.329 m, and the wave scale classification accuracies were, respectively, 91.1%, 99.4%, 86%, 83.3%, 78.9%, and 77.5%. The experimental results validate that the transformer model can achieve continuous and accurate SWH forecasting, as well as accurate wave scale classification and early warning of waves, providing technical support for wave monitoring.

HSPA12A was identified as a key driver in colorectal cancer GWAS loci 10q26.12 and modulated by an enhancer–promoter interaction - Zequn Lu; Linyun Fan; Fuwei Zhang; Chaoqun Huang; Yimin Cai; Can Chen; Gaoyuan Li; Ming Zhang; Jinyu Huang; Caibo Ning; Yanmin Li; Wenzhuo Wang; et al. (Archives of Toxicology, 2023)

Evaluation of cigarette smoke-induced oxidative stress and inflammation in BEAS-2B cells based on a lung microfluidic chip - Jingxian Xue; Zezhi Li; Xiang Li; Chenfeng Hua; Pingping Shang; Junwei Zhao; Kejian Liu; Fuwei Xie (Food and Chemical Toxicology, 2023)

Nanomaterials-modulated Fenton reactions: Strategies, chemodynamic therapy and future trends - Junjie Qi; Guoyong Jiang; Yuqi Wan; Jinghan Liu; Fuwei Pi (Chemical Engineering Journal, 2023)

Earth-abundant Co nanoparticles encapsulated in N-doped hollow carbon sphere for highly selective hydrodeoxygenation of biomass-derived vanillin - Jun Wu; Ming Jin; Yong Li; Junfeng Zhao; Tingting Wang; Yuhang Xie; Liqian Liu; Chengbing Wang; Fuwei Li (Chemical Engineering Journal, 2023)

Non-destructive determination of internal defects in chestnut (Castanea mollissima) during postharvest storage using X-ray computed tomography - Jiahua Wang; Zelin Lu; Xiaofeng Xiao; Mengting Xu; Yuqing Lin; Huang Dai; Xiaodan Liu; Fuwei Pi; Donghai Han (Postharvest Biology and Technology, 2023)

The asymmetric effect of technology shocks on CO2 emissions: a panel analysis of BRICS economies - Jingjing Chen; Fuwei Yang; Yicen Liu; Ahmed Usman (Environmental Science and Pollution Research, 2022)

Sensitive Techniques for POCT Sensing on the Residues of Pesticides and Veterinary Drugs in Food - Lin Liu; Yueying Gao; Jinghan Liu; Ying Li; Ziye Yin; Yuanyuan Zhang; Fuwei Pi; Xiulan Sun (Bulletin of Environmental Contamination and Toxicology, 2021)

Current Progress on Antibiotic Sensing Based on Ratiometric Fluorescent Sensors - Jinghan Liu; Ying Li; Lin Liu; Yueying Gao; Yuanyuan Zhang; Ziye Yin; Fuwei Pi; Xiulan Sun (Bulletin of Environmental Contamination and Toxicology, 2021)

Planting density and N application rate balance maize agronomic and environmental effect - Kun Han; Fuwei Yin; Peng Liu (Nutrient Cycling in Agroecosystems, 2020)

Genome-wide association study of body weight in Wenshang Barred chicken based on the SLAF-seq technology - Fuwei Li; Haixia Han; Qiuxia Lei; Jinbo Gao; Jie Liu; Wei Liu; Yan Zhou; Huimin Li; Dingguo Cao (Journal of Applied Genetics, 2018)

Cytotoxicity and mutagenicity of sidestream cigarette smoke particulate matter of different particle sizes - Xiang Li; Bencheng Lin; Huashan Zhang; Fuwei Xie; Na Ta; Lei Tian; Huimin Liu; Zhuge Xi (Environmental Science and Pollution Research, 2016)

Variation and genetic stability analyses of transgenic TaLEA poplar clones from four different sites in China - Mengran Liu; Shaopeng Yin; Dongjing Si; Longting Shao; Ying Li; Mi Zheng; Fuwei Wang; Shuchun Li; Guifeng Liu; Xiyang Zhao (Euphytica, 2015)